Anterior Cartilage Rasping During Otoplasty Performed With an Adson Brown Cartilage Forceps. Issue 1 (January 2021) - Rauso, Raffaele; Lo Faro, Carmelo; Rugge, Luigi; Califano, Luigi; Tartaro, Gianpaolo
Abstract : Abstract: Protruding ears are a common occurrence and can affect the aesthetics and psychosocial aspects of patients. Hundreds of procedures have been described over the years to correct the 2 main deformities related to protruding ears: conchal hypertrophy and anti-helical fold absence. For the rasping technique, the rasp is inserted posteriorly, from the side where the skin is excised; The ending part of the forceps looks like a small rasp, it worked very well and the surgery was completed without problems The authors think this tip could be a useful "tool" for all the surgeons used to perform cartilage rasping "in case of necessity" when rasp is not available.